2006
DOI: 10.1038/ja.2006.103
|View full text |Cite
|
Sign up to set email alerts
|

Verticipyrone, a New NADH-fumarate Reductase Inhibitor, Produced by Verticillium sp. FKI-1083

Abstract: A new NADH-fumarate reductase inhibitor, verticipyrone, was isolated from the cultured broth of a fungus, Verticillium sp. FKI-1083. The structure was established as (E)-2-methoxy-3,5-dimethyl-6-(3-methyl-2-undecenyl)-4H-pyran-4-one. Verticipyrone exhibited an IC 50 value of 0.88 nM against NADH-fumarate reductase of Ascaris suum. Verticipyrone inhibited both Ascaris and bovine heart complex I, and its synthetic analogue, 8,9-dihydro-8-hydroxyverticipyrone, showed good selectivity against Ascaris complex I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…These three compounds did not inhibit DHT-independent GAPDH gene expression under these conditions (data not shown). Spectinabilin was reported to inhibit Ascaris NADH-fumarate reductase, 14 and we found that it inhibited mitochondrial respiration of tumor cells, but its IC 50 value is about 100 nM. Therefore, inhibition of DHT-induced expression of PSA mRNA by these compounds is not due to nonspecific toxic effect or global RNA synthesis-inhibitory effect, but due to AR antagonistic effect.…”
Section: Structure Elucidation Of Arabilinmentioning
confidence: 75%
“…These three compounds did not inhibit DHT-independent GAPDH gene expression under these conditions (data not shown). Spectinabilin was reported to inhibit Ascaris NADH-fumarate reductase, 14 and we found that it inhibited mitochondrial respiration of tumor cells, but its IC 50 value is about 100 nM. Therefore, inhibition of DHT-induced expression of PSA mRNA by these compounds is not due to nonspecific toxic effect or global RNA synthesis-inhibitory effect, but due to AR antagonistic effect.…”
Section: Structure Elucidation Of Arabilinmentioning
confidence: 75%
“…Structure elucidation was performed using mass spectrometry and NMR methods, and data were compared to that of iromycin A. The non-natural derivatives iromycin AH (13), AM (14), BM (15), AA (16), and BA (17) were prepared from the microbial metabolites iromycin A (7) and B (8) which can be isolated from Streptomyces sp. Dra 17 in reasonable amounts.…”
Section: Organic and Biomolecular Chemistrymentioning
confidence: 99%
“…10 Synthetic MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, 2) and the plant-derived rotenone (3) are now regularly used in cell cultures and model studies of Parkinson's disease. 10,11 The enormous structural diversity of known inhibitors of complex I, which also includes microbial myxalamids (e.g., 4) 12 and piericidins (e.g., 5) 13 as well as the fungal verticipyrone (6), 14 has led to attempts to classify these compounds into three fundamental types based on their presumed different modes of inhibition in the ubiquinone redox cycle and thus, different binding sites. 6 However, current hypotheses of the inhibitor binding domain suggest a common large binding pocket, which is constructed by multiple subunits and has several, partially overlapping binding positions for the structurally diverse inhibitor molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Their vinologous isomers, γ -pyrones, are also involved in many fields of molecular sciences. Such moieties have been identified in the structure of numerous natural products [4, 5], such as the onchitriols I and II [6], petrocortyne C [7], cyercene A [8], verticipyrone [9], the auripyrones A and B [10], or N -acetylaureothamine [11], as but a small sample (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%